2012 13th International Conference on Electronic Packaging Technology &Amp; High Density Packaging 2012
DOI: 10.1109/icept-hdp.2012.6474640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper plating thickness of Ni/Fe alloy leadframe on the thermal performance of Small Outline Transistor (SOT) packages

Abstract: Small Outline Transistor (SOT) packages, due to their low cost and low profile, are widely used in consumer electronics. Ni/Fe alloy (A42) is the most widely used leadframe material of SOT packages because of its low cost, good formability and CTE (coefficient of thermal expansion) match with silicon die. The very small size of SOT packages allow a higher package density on a board, but the small size and close proximity of SOT packages make thermal management difficult The low thermal conductivity of A42, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Attentions have been drawn that package resistance is becoming the main contributor to the total product resistance instead of the intrinsic electrical silicon resistance [1,2]. The relationships between reliability and thermal resistance have been widely investigated [3][4][5], and it was demonstrated that a low thermal resistance can lead to high reliability [6]. Moreover, as the electronic packages are becoming smaller and thinner, there emerges an increasing demand for high signal integrity at high switch speeds.…”
Section: Introductionmentioning
confidence: 99%
“…Attentions have been drawn that package resistance is becoming the main contributor to the total product resistance instead of the intrinsic electrical silicon resistance [1,2]. The relationships between reliability and thermal resistance have been widely investigated [3][4][5], and it was demonstrated that a low thermal resistance can lead to high reliability [6]. Moreover, as the electronic packages are becoming smaller and thinner, there emerges an increasing demand for high signal integrity at high switch speeds.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the influence of copper plating thickness on the thermal performance of SOT packages, a simplified thermal resistance circuit model is proposed and the corresponding mathematical expression of θ ja on function of copper plating thickness is deduced by fitting the model with simulation results using mean squares method [4]. Die cracking and die delamination caused by thermal residual stresses are common and critical issues for microelectronic packages.…”
Section: Introductionmentioning
confidence: 99%